2018
DOI: 10.1093/hmg/ddy210
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mendelian randomization framework elucidates hundreds of CpG sites which may mediate the influence of genetic variants on disease

Abstract: We have undertaken a systematic Mendelian randomization (MR) study using methylation quantitative trait loci (meQTL) as genetic instruments to assess the relationship between genetic variation, DNA methylation and 139 complex traits. Using two-sample MR, we identified 1148 associations across 61 traits where genetic variants were associated with both proximal DNA methylation (i.e. cis-meQTL) and complex trait variation (P < 1.39 × 10−08). Joint likelihood mapping provided evidence that the genetic variant whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 64 publications
1
58
0
Order By: Relevance
“…In addition, our study improved upon some previous MR studies of omics 7 8 by utilising both cis and trans instruments. Several of the approaches (single-cis, multi-cis and trans-only) yielded informative results.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, our study improved upon some previous MR studies of omics 7 8 by utilising both cis and trans instruments. Several of the approaches (single-cis, multi-cis and trans-only) yielded informative results.…”
Section: Discussionmentioning
confidence: 79%
“…Recent MR studies highlight the value of hypothesis-free (“phenome-wide”) MR in building a comprehensive picture of the causal effects of risk factors on disease outcomes 8 34 35 . Given that human proteins represent the major source of therapeutic targets, we sought to mine our results for targets of molecules already approved as treatments or in ongoing clinical development, and which might represent promising candidates for repositioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in its current form, IMAGE is well-suited to analyzing sequencing-based DNA methylation data sets of the size and scale typically generated in recent studies [103]. Thus, it can be flexibly deployed to investigate the genetic architecture of gene regulatory variation, the relative role of genes and the environment in shaping the epigenome, or the mediating role of DNA methylation in linking environmental conditions to downstream phenotypes, including human disease (e.g., via Mendelian randomization or related approaches [104, 105]).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they could be associated with other regulatory regions such as enhancers, for example in association with SNPs. Indeed, GWAS performed in multiple complex diseases have shown that SNPs of susceptibility are enriched in enhancer regions, and DNA methylation could be an intermediary in this process 31,32 . Illustrating this, the presence of differentially methylated sites in the vicinity of known susceptibility loci supports the notion of DNA methylation as an intermediary between genotype and phenotype (mQTLs).…”
Section: Discussionmentioning
confidence: 99%